(untitled) (Marketing Journal, 2025)
This article analyzes the role and importance of strategic marketing approaches in enhancing enterprise competitiveness. It demonstrates that the correct selection and targeted implementation of marketing strategies can ensure a product or serviceʼs advant age in the market. The paper explores approaches to achieving competitive advantage based on the STP model, differentiation strategy, value chain, and digital marketing tools. Based on empirical analysis, the effectiveness of strategic marketing approaches is assessed, and practical recommendations are developed.